Thermal enhancement in magnetized flow of ZnO - SAE50 nanolubricant over a rotating sphere influenced by nonlinear heat generation and thermal radiation - Riaz, Muhammad; Khan, Nargis; Hashmi, M. S.; Sana, Madiha; Alsubaie, A. S. A.; İnç, Mustafa (Elsevier, 2024)
The nanolubricant ZnO - SAE50 is essentially used in a range of industries, including electronics, renewable energy, automotive, and aerospace. Due to its distinct thermal and lubricating characteristics, it can serve a variety of purposes and has the potential to revolutionize a number of technological fields. The prime motive of this study is to introduce ZnO - SAE50 nanolubricant as a flow fluid around a rotating sphere immersed in a Darcy-Forchheimer medium. To control and direct the flow to the desired direction, an external magnetic field is employed. The thermal performance is assessed considering the effects of thermal radiation, nonlinear heat generation and Joule heating. A MATLAB's built-in solver bvp-4c is used to solve the achieved model numerically. The findings disclose that the implementation of an external magnetic field is quite advantageous in adjusting and directing the fluid flow. In order to achieve an excellent thermal performance, the role of thermal radiations and nonlinear heat generation is pivotal. Furthermore, ZnO - SAE50 nanolubricant maximizes heat transmission while conventional SAE50 is ineffective in achieving optimum heat transfer rates.
Keywords: Rotating sphere; nanolubricant; MHD; Darcy-forchheimer medium; Nonlinear heat generation; Bvp-4c solver